The Relationship Between Job Attitudes and the Decision to Retire - Schmitt, Neal; McCune, Joseph T. (Academy of Management Journal, 1981)
For a group of civil service employees, discriminant analysis indicated that job attitude and financial variables contributed significantly to the prediction of retirement status even when the effects of various demographic variables, including job levels and education, were removed. Health was not a statistically significant factor.